The Impact of Therapist Sexual Orientation on Occupational Therapy Outcomes: A Focus on LGBTQ+ Therapists, - Myrto Patagia Bakaraki; Theofanis Dourbois (Dialogues in Clinical Neuroscience & Mental Health)
Background: This study looks at the impact of therapist sexual orientation on outcomes in occupational therapy (OT), specifically for LGBTQ+ therapists. The research examines how therapists’ sexual orientation affects the therapeutic relationship, treatment success and patient satisfaction. Methods: Mixed methods design, 753 patient surveys and 20 therapist and 20 patient interviews. Quantitative analysis looked at satisfaction, quality of care and therapeutic relationship, qualitative looked at therapist experiences and patient perceptions. Results: Treatment outcomes not affected by therapist’s sexual orientation. LGBTQ+ visibility and supportive environments increase inclusivity, reduce stigma and build therapeutic alliance. LGBTQ+ patients felt more understood and connected when treated by LGBTQ+ therapists. Conclusions: Sexual orientation doesn’t affect outcomes but visibility and inclusion for LGBTQ+ therapists makes for a more accepting space. Diversity, cultural competence and anti-discrimination policies matter.